Associação entre terapia antirretroviral e o risco cardiovascular em pessoas que vivem com HIV/AIDS - Costa, Raphael Silva Nogueira (2016)
The introduction of highly active antiretroviral therapy (HAART) for the treatment of HIV-infected individuals brought a dramatic change in the natural course of the disease, leading to increased prevalence of diseases not directly related to HIV such as Diabetes Mellitus and cardiovascular diseases in these individuals. In this context, this study aimed to evaluate the impact of HAART on the cardiovascular risk of people living with HIV/AIDS registered in the Municipal Reference Center of Sexually Transmitted Diseases/HIV/AIDS in the municipality of Feira de Santana, Bahia. This cross-sectional study was carried out through analysis of medical records of patients admitted between 2010 and 2014. The data collection form used contained questions relating to sociodemographic factors, cardiovascular risk factors, and characteristics related to HIV infection. Data were analyzed using STATA version 11 for Windows. The results support an association between the use of HAART and increased overall cardiovascular risk. The following factors were also associated with increased overall cardiovascular risk: age >40 years; male; paid employment; smoking; blood pressure ≥140/90 mm Hg; cholesterol ≥ 240 mg/dl; triglycerides ≥ 200mg/dl; glucose ≥ 110mg/dl; change in the HAART scheme; and viral load < 10,000 copies/mm3.